Cooking Pumpkin Stick Cooking Training for Empowerements of Family Walfare Mothers as an Effort to Improve the Economy in Jatibanjar Village, Ploso District, Jombang Regency - Kahan Tony Hendrawan; Nurdian Ahmad; Muhammad Saibani Wiyanto; Khariza Rahmania Putri; Sabbahul Putri Wulandari; Elinda Putri Sari; Hanum Muyasaroh (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2022)
Cooking skills training is carried out in order to empower the community amid the weakening economy due to the Covid-19 outbreak in Indonesia which has not subsided until now, it is hoped that this training will be able to create an independent and empowered community so that it can be a step in tackling the problems of poverty that occur. This training is carried out by means of demonstration (live practice) which is intended so that participants can directly ask questions and discuss related to the material presented. The food product processing skills taught in this training are the type of food, namely Pumpkin Stick. Participants of the cooking skills training are women members of the Jatibanjar Village PKK with an average age of 30-50 years, totaling 35 people and it will be held on Thursday, January 20, 2022 starting at 09.00 - finished, at the Jatibanjar Balaidesa residence. The results obtained from this cooking training are the increased skills of PKK women in Jati Banjar village to process simple foods in increasing the economy in utilizing pumpkin as food that has a selling value.